Penggunaan Musik Klasik sebagai Media dalam Meningkatkan Kecerdasan Emosional terhadap Anak Usia Balita 0-5 Tahun - Evi Sondang Pangaribuan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2021)
Children's behavior patterns are vulnerable to environmental influences. The attitudes and responses given by children are very much determined by the patterns of upbringing and the patterns of students from their environment, especially in the toddler years (0-5 years) which is called the golden age. This is a very important period because most of the children's brain development is dominated at that time, reaching 80%, while the next 20% will develop after an early age to 18 years of age. Children's emotional intelligence is a very important aspect to be developed, because it will determine children's behavior in the future. One of the appropriate stimuli is by using music, in this case classical music. Where music is the element closest to human life.